2015
DOI: 10.1007/s00299-015-1781-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the dark green islands of cucumber mosaic virus infected Nicotiana tabacum

Abstract: There are significant differences between the DGIs and LGTs. Additionally, most of the characteristics indicate that the DGIs are more similar to recovered tissue and can resist viral attacks. Dark green islands (DGIs) surrounded by light green tissues (LGTs) are common leaf symptoms of plants that are systemically infected by various mosaic viruses. We performed cytological, physiological and molecular biological analyses of the DGIs and LGTs in cucumber mosaic virus-infected Nicotiana tabacum leaves. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 71 publications
3
15
0
Order By: Relevance
“…In symptomatic chlorotic tissues of virus-infected plants the PRGs are down-regulated. As reported before, when light-dark mosaic symptoms occurred, photosynthetic apparatus was damaged only in chlorotic areas, the dark islands retained intact chloroplast structure and function (Chen et al, 2015). PPV-Rec isolate BOR-3 used in our experiments induced only dark green areas around the main veins on N. benthamiana leaves and slight downrolling of the leaf blades.…”
Section: Resultsmentioning
confidence: 61%
“…In symptomatic chlorotic tissues of virus-infected plants the PRGs are down-regulated. As reported before, when light-dark mosaic symptoms occurred, photosynthetic apparatus was damaged only in chlorotic areas, the dark islands retained intact chloroplast structure and function (Chen et al, 2015). PPV-Rec isolate BOR-3 used in our experiments induced only dark green areas around the main veins on N. benthamiana leaves and slight downrolling of the leaf blades.…”
Section: Resultsmentioning
confidence: 61%
“…Our previous study also suggested that there are significant differences between DGIs and LGTs in terms of physiology, biochemistry and molecular biology [13]. Additionally, DGIs were more similar to recovered tissues and could resist viral infection better than LGTs, which is a prediction that is supported by most DGI characteristics [13]. …”
Section: Introductionmentioning
confidence: 84%
“…The Chl fluorescence parameters of the leaves were measured using an FMS2 fluorescence meter (PAM-2100, Walz, Germany) according to previously described methods [13]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations